Adhesion of Salmonella to Pancreatic Secretory Granule Membrane Major Glycoprotein GP2 of Human and Porcine Origin Depends on FimH Sequence Variation - Kolenda, Rafał; Burdukiewicz, Michał; Schiebel, Juliane; Rödiger, Stefan; Sauer, Lysann; Szabo, Istvan; Orłowska, Aleksandra; Weinreich, Jörg; Nitschke, Jörg; Böhm, Alexander; Gerber, Ulrike; Roggenbuck, Dirk; et al. (Frontiers in Microbiology, 2018)
Bacterial host tropism is a primary determinant of the range of host organisms they can infect. Salmonella serotypes are differentiated into host-restricted and host-adapted specialists, and host-unrestricted generalists. In order to elucidate the underlying molecular mechanisms of host specificity in Salmonella infection, we investigated the role of the intestinal host cell receptor zymogen granule membrane glycoprotein 2 (GP2), which is recognized by FimH adhesin of type 1 fimbriae found in Enterobacteriaceae. We compared four human and two porcine GP2 isoforms. Isoforms were expressed in Sf9 cells as well as in one human (HEp-2) and one porcine (IPEC-J2) cell line. FimH genes of 128 Salmonella isolates were sequenced and the ten identified FimH variants were compared regarding adhesion (static adhesion assay) and infection (cell line assay) using an isogenic model. We expressed and characterized two functional porcine GP2 isoforms differing in their amino acid sequence to human isoforms by approximately 25%. By comparing all isoforms in the static adhesion assay, FimH variants were assigned to high, low or no-binding phenotypes. This FimH variant-dependent binding was neither specific for one GP2 isoform nor for GP2 in general. However, cell line infection assays revealed fundamental differences: using HEp-2 cells, infection was also FimH variant-specific but mainly independent of human GP2. In contrast, this FimH variant dependency was not obvious using IPEC-J2 cells. Here, we propose an alternative GP2 adhesion/infection mechanism whereby porcine GP2 is not a receptor that determined host-specificity of Salmonella. Salmonella specialists as well as generalists demonstrated similar binding to GP2. Future studies should focus on spatial distribution of GP2 isoforms in the human and porcine intestine, especially comparing health and disease.